Genome-wide DNA Methylation and RNAseq Analyses Identify Aberrant Signalling Pathways in Focal Cortical Dysplasia (FCD) Type II. Issue 1 (December 2018) - Dixit, Aparna; Sharma, Devina; Tripathi, Manjari; Srivastava, Arpna; Paul, Debasmita; Prakash, Deepak; Sarkar, Chitra; Kumar, Krishan; Banerjee, Jyotirmoy; Chandra, P.
Abstract Focal cortical dysplasia (FCD) is one of the most common pathologies associated with drug-resistant epilepsy (DRE). The pharmacological targets remain obscured, as the molecular mechanisms underlying FCD are unclear. Implications of epigenetically modulated aberrant gene expression in disease progression are reported in various DRE pathologies except FCD. Here we performed genome-wide CpG-DNA methylation profiling by methylated DNA immunoprecipitation (MeDIP) microarray and RNA sequencing (RNAseq) on cortical tissues resected from FCD type II patients. A total of 19088 sites showed altered DNA methylation in all the CpG islands. Of these, 5725 sites were present in the promoter regions, of which 176 genes showed an inverse correlation between methylation and gene expression. Many of these 176 genes were found to belong to a cohesive network of physically interacting proteins linked to several cellular functions. Pathway analysis revealed significant enrichment of receptor tyrosine kinases (RTK), EGFR, PDGFRA, NTRK3, and mTOR signalling pathways. This is the first study that investigates the epigenetic signature associated with FCD type II pathology. The candidate genes and pathways identified in this study may play a crucial role in the regulation of the pathogenic mechanisms of epileptogenesis associated with FCD type II pathologies.